2021
DOI: 10.1111/tri.13858
|View full text |Cite
|
Sign up to set email alerts
|

Number of hepatocellular carcinoma nodules in patients listed for liver transplantation within alpha‐fetoprotein score: a new prognostic risk factor

Abstract: In France, the listing for liver transplantation (LT) for hepatocellular carcinoma (HCC) requires an AFP score ≤2. This study evaluates whether the number of nodules assessed immediately before LT has a prognostic value among patients already listed within AFP score. Among 143 recipients transplanted with an AFP score ≤2 between 2013 and 2017 in our center, the number of nodules was considered at listing on the waiting list and at last imaging before LT. We compared the overall survival (OS) and disease-free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The prognosis of NV-HCC patients is closely related to the number of nodules in the liver. Mazzotta et al reported that patients who had more than 5 HCC nodules during the waiting period had a high risk of post liver transplantation recurrence and death [ 27 ]. Markers of the inflammatory response, including LMR, SLR, lymphocytes, NLR, and CRP, play important roles in the progression of many cancers [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of NV-HCC patients is closely related to the number of nodules in the liver. Mazzotta et al reported that patients who had more than 5 HCC nodules during the waiting period had a high risk of post liver transplantation recurrence and death [ 27 ]. Markers of the inflammatory response, including LMR, SLR, lymphocytes, NLR, and CRP, play important roles in the progression of many cancers [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of NV-HCC patients is closely related to the number of nodules in the liver. Mazzotta et al reported that the patients had high risk of post liver transplantation recurrence and death who had more than 5 HCC nodules during the waiting period [27]. Markers of in ammatory response, including LMR, SLR, lymphocytes, NLR, and CRP, play important roles in the progression of many cancers [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The UCSF criteria might be considered a reasonable upper limit for applying downstaging protocols on a solely morphometric basis. However, in the all-comers cohort, a proportion of patients can be cured by LT, although the likelihood is clearly lower ( 20 , 21 ). Considering this, it might be ‘too restrictive’ or more precisely ‘too unspecific’, if patient selection for downstaging is only based on tumor size and number.…”
Section: Still Not Outdated: Morphometric Parameters—should There Be ...mentioning
confidence: 96%